Entanglement in smart hydrogels: fast response time, anti-freezing and anti-drying - Feng, Yuqin (2023)
The common techniques to improve hydrogel's mechanical properties include increasing crosslinking density and forming crosslinked double-network hydrogel, which may cause some hydrogels to lose their smart functionalities. Inspired by entanglement-induced strengthening, a simple approach to introducing hydroxypropyl cellulose (HPC) fibers entangled with different smart hydrogel matrix systems are reported. Different from the conventional methods which hinder the movement of the polymer network, through entanglement with HPC fibers, the composite hydrogel shows both improved Young's modulus and toughness and more importantly improved smart functionalities including response speed, anti-drying, and anti-freezing capabilities and cycle stability. This strategy provides a new design rule to fabricate durable and strengthened smart hydrogels which can be used in smart windows, sensors, and soft robots.